Determination of Information Security Using Cryptography and Image Steganography - G. Mallikharjuna Rao (Advanced Aspects of Engineering Research Vol. 16, 2021)
Hackers are usually prepared to hack confidential documents for their vested interests. The most difficult task is to establish a secure link between the secret message and image quality. The proposed scheme combines cryptography and image steganography techniques to avoid illegal attacks by an unknown person. This scheme will enable image security and message security. The International Data Encryption Algorithm (IDEA) cryptographic algorithms and Discrete Cosine Transform (DCT) based steganography algorithms based functional approach. The purpose of cryptography is to encrypt and decrypt the document. Steganography is the technique of hiding documents within an image with increasing payload for the secure transmission of confidential data over the internet. In this paper, we present a single application to hide the information by the sender, which is an essential document and secret file. The form will be invisible to an unauthorized person. PSNR of 90.06 dB with a payload of 52,400 bytes of information in an image.